2019
DOI: 10.3390/cells8111314
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the Peripheral Immune System Limits the Central Immune Response Following Cuprizone-Feeding: Relevance to Modelling Multiple Sclerosis

Abstract: Cuprizone (CPZ) preferentially affects oligodendrocytes (OLG), resulting in demyelination. To investigate whether central oligodendrocytosis and gliosis triggered an adaptive immune response, the impact of combining a standard (0.2%) or low (0.1%) dose of ingested CPZ with disruption of the blood brain barrier (BBB), using pertussis toxin (PT), was assessed in mice. 0.2% CPZ(±PT) for 5 weeks produced oligodendrocytosis, demyelination and gliosis plus marked splenic atrophy (37%) and reduced levels of CD4 (44%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
107
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(118 citation statements)
references
References 173 publications
(258 reference statements)
11
107
0
Order By: Relevance
“…While there have been numerous reports of CPZ being used to study demyelination, these have not established the involvement of peripheral T-cells at the sites of CPZ-induced demyelination in the CNS (Remington et al, 2007;Partridge et al, 2016;Traka et al, 2016;Tejedor et al, 2017;Sen et al, 2019a). It was thought that as CPZ does not induce a breach of the blood-brain barrier (BBB), T-cells have no access to the CNS (Remington et al, 2007;Skripuletz et al, 2011;Tejedor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…While there have been numerous reports of CPZ being used to study demyelination, these have not established the involvement of peripheral T-cells at the sites of CPZ-induced demyelination in the CNS (Remington et al, 2007;Partridge et al, 2016;Traka et al, 2016;Tejedor et al, 2017;Sen et al, 2019a). It was thought that as CPZ does not induce a breach of the blood-brain barrier (BBB), T-cells have no access to the CNS (Remington et al, 2007;Skripuletz et al, 2011;Tejedor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It was thought that as CPZ does not induce a breach of the blood-brain barrier (BBB), T-cells have no access to the CNS (Remington et al, 2007;Skripuletz et al, 2011;Tejedor et al, 2017). However, even when the BBB was breached using pertussis toxin (PT), CPZ evoked marked CNS demyelination, gliosis and changes in the abundance of proteoforms involved in metabolism, immune and synaptic functions, without detectable T-cell infiltration (Sen et al, 2019a). Studies have indicated that the apparent failure to trigger a T-cell-mediated CNS immune response is due to CPZ-induced atrophy of the thymus (the organ responsible for T-cell maturation and differentiation) and spleen (the organ of T and B lymphocyte production; Solti et al, 2015;Martin et al, 2018;Sui et al, 2019;Sen et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The research includes using animal models to help understand the demyelination and remyelination mechanisms, facilitating the study of cellular responses taking place in this process, and providing a robust platform for elucidating putative therapeutic targets. However, there is the limitation that no current animal model faithfully replicates the myriad of symptoms seen in the clinical condition of MS [2,7].…”
Section: Introductionmentioning
confidence: 99%